The Implementation of Pesantren Values and Traditions in Shaping The Social Dynamics of Students at Al Mu'allim Vocational High School, Al-Fiel Islamic Boarding School, Kesugihan, Cilacap, Indonesia - Masruri; Mulyoto; A. Dardiri Hasim (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study examines the implementation of pesantren values and traditions and their contribution to the social dynamics of students at Al Mu'allim Vocational High School within Al-Fiel Islamic Boarding School, Kesugihan, Cilacap, Indonesia, in 2025. The research aims to explore how Islamic boarding school values are internalized through daily traditions and how these practices influence students' social interactions, discipline, cooperation, leadership, and moral character. A qualitative case study approach was employed using observations, in-depth interviews, and document analysis. The collected data were analyzed through data reduction, data display, and conclusion drawing following the interactive model. The findings reveal that the integration of pesantren values and traditions significantly strengthens students' social cohesion, religious commitment, responsibility, and adaptive behavior within the school environment. The study contributes to the discourse on Islamic education by demonstrating that pesantren-based cultural practices serve as an effective model for fostering positive social dynamics and character development in vocational education.